2014
DOI: 10.1002/eqe.2423
|View full text |Cite
|
Sign up to set email alerts
|

Welded end‐slot connection and debonding layers for buckling‐restrained braces

Abstract: SUMMARY The debonding mechanism has a significant effect on the performance of a buckling‐restrained brace (BRB). In this paper, a method for estimating the compression strength adjustment factor for any given BRB core strain is presented. Experimental investigations were conducted on four BRBs to examine the efficiency of four different debonding materials in reducing the difference between the cyclic peak compression and tension. Test results indicate that chloroprene rubber is very easy to install and very … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
92
0

Year Published

2014
2014
2017
2017

Publication Types

Select...
7

Relationship

6
1

Authors

Journals

citations
Cited by 72 publications
(93 citation statements)
references
References 16 publications
1
92
0
Order By: Relevance
“…The frame tests by Lin et al [15], Chou et al [16], and Palmer et al [17] showed that in-plane frame action force at the beam-column-gusset interface was observed. These findings [15][16][17][18][19][20][21] all highlighted the negative effect of braced frame seismic deformations on the performance of BRB connection zones. The gusset plate design considering the combined effect of brace action and frame action forces was investigated theoretically and numerically [18][19][20].…”
Section: Introductionmentioning
confidence: 94%
See 1 more Smart Citation
“…The frame tests by Lin et al [15], Chou et al [16], and Palmer et al [17] showed that in-plane frame action force at the beam-column-gusset interface was observed. These findings [15][16][17][18][19][20][21] all highlighted the negative effect of braced frame seismic deformations on the performance of BRB connection zones. The gusset plate design considering the combined effect of brace action and frame action forces was investigated theoretically and numerically [18][19][20].…”
Section: Introductionmentioning
confidence: 94%
“…The subassemblage tests by Tremblay et al [14] showed that BRB end rotation would cause additional inplane flexural stress on BRB casing. The gusset plate design considering the combined effect of brace action and frame action forces was investigated theoretically and numerically [18][19][20]. The frame tests by Lin et al [15], Chou et al [16], and Palmer et al [17] showed that in-plane frame action force at the beam-column-gusset interface was observed.…”
Section: Introductionmentioning
confidence: 99%
“…Based on previous experimental and analytical studies, the effective elastic stiffness K eff of a typical BRB in a structural frame can be computed from three springs connected in series [21] as: ) 468 671 25 35 397 530 394 483 398 521 90 Note: f y and F y are steel yield strengths; f u and F u are steel tensile strengths; f c is concrete or mortar compressive strengths. Based on previous experimental and analytical studies, the effective elastic stiffness K eff of a typical BRB in a structural frame can be computed from three springs connected in series [21] as: ) 468 671 25 35 397 530 394 483 398 521 90 Note: f y and F y are steel yield strengths; f u and F u are steel tensile strengths; f c is concrete or mortar compressive strengths.…”
Section: Design Of Buckling-restrained Brace and Steel Framementioning
confidence: 99%
“…Practical methods of utilizing BRB technology are well developed. In comparison with butt-spliced or lap-spliced BRBs, slot-spliced BRBs have more compact joints, greater BRB end stability [3,23,24,26] and higher fatigue life because of increased yield region length [21,25]. In comparison with butt-spliced or lap-spliced BRBs, slot-spliced BRBs have more compact joints, greater BRB end stability [3,23,24,26] and higher fatigue life because of increased yield region length [21,25].…”
Section: Design Of Buckling-restrained Brace and Steel Framementioning
confidence: 99%
“…The letter 'W' stands for the welded BRB end details ( Figure 9a); meanwhile, letters 'R' (Figure 9b), 'F' (Figure 9c), and 'C' (Figure 9d) stand for the specimens using the pinned end connections with the ribbed, flanged, and cover-plated joint sections, respectively. In addition, in order to investigate the effects of the debonding layer thickness on the local bulging failure, the chloroprene rubber (CR) debonding layer [11] thickness in the R25G1-250-IN and F25G4-160-IN were 1 mm and 4 mm, respectively. The second last letter in the IDs stands for the applied loading type, which is described later.…”
Section: Experimental Programmentioning
confidence: 99%